2009
DOI: 10.1371/journal.pone.0005602
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tuberculosis, HIV and Respiratory Symptoms in Two Zambian Communities: Implications for Tuberculosis Control in the Era of HIV

Abstract: BackgroundThe Stop TB Partnership target for tuberculosis is to have reduced the prevalence of tuberculosis by 50% comparing 2015 to 1990. This target is challenging as few prevalence surveys have been conducted, especially in high burden tuberculosis and HIV countries. Current tuberculosis control strategies in high HIV prevalent settings are therefore based on limited epidemiological evidence and more evidence is needed from community-based surveys to inform improved policy formulation.Methods and Findings80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(143 citation statements)
references
References 21 publications
5
133
3
2
Order By: Relevance
“…Specifically, in any given setting, TB transmission may occur primarily from people who are not sufficiently ill to seek care 49,50 ; those who are seeking care, but have symptoms (for example, a mild cough) not specific to TB 51 ; or those with severe or prolonged symptoms, but who test negative for TB and are therefore not treated (Fig. 1b).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, in any given setting, TB transmission may occur primarily from people who are not sufficiently ill to seek care 49,50 ; those who are seeking care, but have symptoms (for example, a mild cough) not specific to TB 51 ; or those with severe or prolonged symptoms, but who test negative for TB and are therefore not treated (Fig. 1b).…”
Section: Methodsmentioning
confidence: 99%
“…[44][45][46][47][48] HIV-positive individuals had 1·7-4·4 times higher prevalence of culture-positive tuberculosis and 0·8-3·5 times higher prevalence of undiagnosed smearpositive tuberculosis than did HIV-negative individuals: 0-34% of the total burden of smear-positive disease was directly attributable to HIV. [44][45][46][47][48] Most of these patients reported no previous contact with health services, which is consistent with long-term infectiousness before presentation at health facilities.…”
Section: Intensifi Ed Case Fi Nding In the Communitymentioning
confidence: 99%
“…[44][45][46][47][48] HIV-positive individuals had 1·7-4·4 times higher prevalence of culture-positive tuberculosis and 0·8-3·5 times higher prevalence of undiagnosed smearpositive tuberculosis than did HIV-negative individuals: 0-34% of the total burden of smear-positive disease was directly attributable to HIV. [44][45][46][47][48] Most of these patients reported no previous contact with health services, which is consistent with long-term infectiousness before presentation at health facilities. 14 Findings from two studies in Zimbabwe showed that in populations with high prevalence of HIV, provision of easy access to tuberculosis diagnosis in occupational clinics 44 or in outreach facilities 49 can substantially reduce undiagnosed tuberculosis (to 0·3% and 0·4% culture-positive disease, and to 0·1% and 0·2% smear-positive disease, respectively).…”
Section: Intensifi Ed Case Fi Nding In the Communitymentioning
confidence: 99%
See 2 more Smart Citations